Pengaruh Penggunaan Model Pembelajaran Think Pair Share Terhadap Hasil Belajar Sejarah Siswa Kelas XI - Inggrid Novita Kandi; Muhammad Basri; Valensy Rachmedita (FKIP UNIVERSITAS LAMPUNG, 2019)
The purpose of this paper is to determine the effect of the use of the Think Pair Share Model on the Historical Learning Outcomes of eleventh grade Social students at SMA Negeri 13 Bandar Lampung in Academic Year 2019/2020